RLS-associated MEIS transcription factors control distinct processes in human neural stem cells - Volker Kittke; Chen Zhao; Daniel D. Lam; Philip Harrer; Wojciech Krezel; Barbara Schormair; Konrad Oexle; Juliane Winkelmann (Scientific Reports)
Abstract MEIS1 and MEIS2 encode highly conserved homeodomain transcription factors crucial for developmental processes in a wide range of tissues, including the brain. They can execute redundant functions when co-expressed in the same cell types, but their roles during early stages of neural differentiation have not been systematically compared. By separate knockout and overexpression of MEIS1 and MEIS2 in human neural stem cells, we find they control specific sets of target genes, associated with distinct biological processes. Integration of DNA binding sites with differential transcriptomics implicates MEIS1 to co-regulate gene expression by interaction with transcription factors of the SOX and FOX families. MEIS1 harbors the strongest risk factor for restless legs syndrome (RLS). Our data suggest that MEIS1 can directly regulate the RLS-associated genes NTNG1, MDGA1 and DACH1, constituting new approaches to study the elusive pathomechanism or RLS.